2022
DOI: 10.1021/acs.nanolett.1c04434
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Delocalized Ti 3d Electrons in Ultrathin Single-Crystal SrTiO3

Abstract: Strontium titanate (STO), with a wide spectrum of emergent properties such as ferroelectricity and superconductivity, has received significant attention in the community of strongly correlated materials. In the strain-free STO film grown on the SrRuO3 buffer layer, the existing polar nanoregions can facilitate room-temperature ferroelectricity when the STO film thickness approaches 10 nm. Here we show that around this thickness scale, the freestanding STO films without the influence of a substrate show the tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Enhanced tetragonality was also observed in ultrathin freestanding STO thin films by Chiu et al. [ 119 ] In their work, the authors showed that STO thin films below 10 nm undergo through a transformation from cubic to tetragonal structure when released from the substrate. This phase is characterized by a displacement of Ti atoms from the TiO 6 octahedron center and by the appearance of delocalized electrons.…”
Section: Emerging Functionalities In Freestanding Perovskite Thin Filmsmentioning
confidence: 78%
“…Enhanced tetragonality was also observed in ultrathin freestanding STO thin films by Chiu et al. [ 119 ] In their work, the authors showed that STO thin films below 10 nm undergo through a transformation from cubic to tetragonal structure when released from the substrate. This phase is characterized by a displacement of Ti atoms from the TiO 6 octahedron center and by the appearance of delocalized electrons.…”
Section: Emerging Functionalities In Freestanding Perovskite Thin Filmsmentioning
confidence: 78%
“…Similarly, many other physical phenomena in ultrathin films and heterostructures can be explained as, for example, the enhanced tetragonality in various perovskites, such as PbTiO 3 , BaTiO 3 , and SrTiO 3 . 49 This involves the electron localization in the out-of-plane π-bonding orbitals which favors the hybridization with the O 2p orbitals strengthening the tetragonal distortion. 50,51 Similarly, it can be expected that the suppression/enhancement of octahedral rotations in perovskite-based heterostructures can be explained by the same hybridization preference upon confinement.…”
Section: ■ Discussionmentioning
confidence: 99%